PENDEKATAN KOMPREHENSIF DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Joko Wahono; Intan Kusumawati; Ahmad Nasir Ari Bowo (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The values ​​of the national character become an important problem if there is still a disgraceful attitude or behavior carried out by a person in his daily life which results in disrupting the life of the community, nation and state. The rapid development of times and technology without good character or behavior will be a problem. The attitudes and behavior of a student that we often encounter, such as fights between students, brawls, drug abuse, drinking and promiscuity will have a negative impact on the development of student character. Synergy is needed between parents, teachers and the community in character building and development. In Pancasila and Citizenship Education aims to make someone a good citizen, have character and make a human being who is democratic and has Pancasila values. The formation of student or student character cannot be obtained instantly, of course, through a process according to a person's stages of development. Forming a character takes a continuous amount of time which eventually becomes an expected character. A comprehensive approach will be able to develop and make someone have good character. The formation and development of character with a comprehensive approach, namely through inculcation or planting of values, giving role models, facilitation ​​and the development of skills (soft skill).